Method for inhibiting shuttle effect of positive active material of zinc-based halogen battery

By constructing a positively charged CEI layer on the surface of the iodine positive electrode of the zinc-based halogen battery, the problems of low loading and easy diffusion of halogen positive electrode active materials are solved, and the effects of high energy density and long cycle life are achieved.

CN119725541APending Publication Date: 2025-03-28CHINA RAILWAY SEVENTH GROUP FIFTH ENGINEERING CO LTD +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411926665.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The load of the halogen positive electrode active substance in zinc-based halide batteries is low, resulting in limited battery energy density, and weak adsorption between the positive electrode substrate and the active substance, resulting in easy diffusion of the active substance, causing self-discharge and reduced Coulomb efficiency.

Method used

A positively charged CEI layer is constructed in situ on the surface of the iodine positive electrode. Through surface charge regulation, the positively charged CEI layer and the polyiodine negative ions in the positive electrode are electrostatically adsorbed, thereby inhibiting the shuttle effect of the iodine active substance.

Benefits of technology

By building a high-load iodine positive electrode, the iodine load and adsorption effect are significantly improved, the energy density and cycle stability of the battery are enhanced, and the life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725541A_ABST
    Figure CN119725541A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of material chemistry, and discloses a method for inhibiting a shuttle effect of a positive active material in a zinc-based halogen battery. A CEI layer with positive charges is constructed on the surface of an iodine positive electrode in situ, and iodine active species with negative charges are fixed by utilizing a strong electrostatic adsorption effect. A complete technical scheme including preparation of an electrode material and construction of a CEI layer is elaborated in detail, and experiments prove that the technology remarkably improves the surface capacity and the energy density of the zinc-iodine battery, effectively solves the problem of poor battery performance caused by insufficient iodine loading capacity and shuttling of active substances in the prior art, and has a wide application prospect. And the method can be popularized and applied to other zinc-based halogen batteries, and has important significance in improving the overall performance of the zinc-based halogen batteries and expanding the application range of the zinc-based halogen batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical materials, and in particular relates to a method for inhibiting the shuttle effect of positive electrode active substances in zinc-based halogen batteries. Background Art

[0002] Aqueous zinc-based batteries have become a hot topic of research due to their high safety, excellent cost-effectiveness, high energy density and simple preparation process. Among the positive electrode materials of zinc-based batteries, halogen positive electrodes, especially iodine positive electrodes, have attracted much attention. They have high theoretical capacity and output voltage, and have great potential in improving battery energy density. The conversion reaction of iodine-based positive electrodes is highly reversible and has excellent reaction kinetics, which makes zinc-based halogen batteries outstanding in terms of cycle stability and high power density, and have broad application prospects. However, halogen positive electrodes encounter bottlenecks in increasing iodine loading and stable fixation on the positive electrode substrate. At present, the loading amount of active substances in halogen positive electrodes is low, which limits the improvement of the overall energy density of the battery. At the same time, the adsorption between the positive electrode substrate and the active substance is weak, which makes the active substance easy to diffuse into the electrolyte and pass through the diaphragm to reach the negative electrode, causing serious self-discharge and a significant reduction in Coulomb efficiency. These problems are more significant under high load conditions, seriously affecting battery performance. Although strategies such as improving cathode materials, optimizing electrolytes and designing separators have been used to suppress the shuttling effect of iodine active substances in zinc-iodine batteries, the iodine loading has not yet reached an ideal level, and there has been no research on constructing an artificial cathode-electrolyte interface (CEI) layer in zinc-iodine batteries. Therefore, the development of this artificial CEI layer is extremely critical to improving battery performance and life. Summary of the invention

[0003] The present invention provides a method for inhibiting the shuttling effect of the positive electrode active material of a zinc-based halogen battery, comprising in-situ constructing a positively charged CEI layer on the surface of an iodine positive electrode, and by regulating the surface charge, causing the positively charged CEI layer to generate electrostatic adsorption with polyiodine anions in the positive electrode, so as to inhibit the shuttling effect of the iodine active material under high load conditions.

[0004] Furthermore, the positively charged CEI layer is constructed by the following steps: uniformly dispersing the positively charged organic polymer in water, uniformly coating it on the surface of the iodine positive electrode by drop coating, and vacuum drying to obtain a high-loaded iodine positive electrode with a positively charged CEI layer.

[0005] Furthermore, the high-loaded iodine positive electrode constructed with a CEI layer is prepared by the following steps:

[0006] Activated carbon (AC), Ketjen black and binder polyvinylidene fluoride (PVDF) were uniformly dispersed in an organic solvent N-methyl-2-pyrrolidone (NMP) at a mass ratio of 7:2:1, and stirred at room temperature for 24 hours to prepare a uniformly dispersed mixed coating liquid;

[0007] The mixed coating liquid prepared in step (1) was applied to the current collector titanium mesh as the host material of the iodine active substance, and dried at 80°C until the organic solvent NMP was completely evaporated. The loading amount of the host material after drying was about 15.5 mg / cm 2 ;

[0008] Using a ZnI2+KI mixed solution as the electrolyte, a two-electrode constant current electroplating method was used to deposit iodine on the titanium mesh coated with the host material prepared in step (2), and then vacuum dried at room temperature to prepare a high-loaded iodine positive electrode. The iodine loading of the positive electrode after drying was about 14.4 mg / cm 2 ;

[0009] The organic polymer containing positive charge is dispersed in water, uniformly dispersed by ultrasonic treatment, and uniformly coated on the surface of the iodine positive electrode by drop coating. After vacuum drying, a high-loaded iodine positive electrode with a positively charged CEI layer can be obtained. The preferred CEI layer loading is 1.1 mg / cm 2 .

[0010] Furthermore, the concentrations of ZnI2 and KI in the electrolyte were both 0.5 M, the electroplating time was 31.0 min, and the current was 6 mA / cm 2 .

[0011] Furthermore, the dispersion amount of the positively charged polymer in water in the step is 10 mg / mL.

[0012] On the other hand, the present invention also provides a high-loaded iodine positive electrode with a CEI layer prepared by the method, wherein the iodine active material loading is 14.4 mg cm -2 , the corresponding CEI layer loading is 1.1 mg cm -2 .

[0013] On the other hand, the present invention also provides a zinc-iodine battery, comprising the high-load iodine positive electrode constructed with a CEI layer, a zinc sheet negative electrode, a 2M ZnSO4 electrolyte and a glass fiber separator.

[0014] On the other hand, the application of the method for constructing a positively charged CEI layer in zinc-based halogen batteries is to construct a positively charged CEI layer on the surface of the iodine positive electrode, and utilize the strong physical and chemical adsorption between the CEI layer and the iodine active substance to improve the loading capacity of the iodine positive electrode, thereby improving the energy density of the zinc-based halogen battery.

[0015] On the other hand, the zinc-based halogen battery is a zinc-bromine battery, which improves the performance of the zinc-bromine battery by constructing a positively charged CEI layer on the surface of the bromine positive electrode to prevent the shuttling of bromine active substances.

[0016] Beneficial technical effects of the invention:

[0017] The present invention has many significant beneficial effects. First, by constructing a positively charged CEI layer on the surface of the iodine positive electrode, and by means of the strong physical and chemical adsorption effect between the CEI layer and the polyiodide ions, a high-loaded iodine positive electrode is successfully constructed, achieving high energy density of the whole battery and expanding the battery application scenarios. Second, the introduction of a positively charged CEI layer at the positive electrode forms a strong physical and chemical adsorption effect with the halogen active substance, which greatly enhances the adsorption effect of the host material on iodine and effectively reduces the loss of active substances. Third, the construction of a high-loaded iodine positive electrode improves the utilization rate of the host material, thereby achieving a high energy density at the level of the whole battery, allowing the battery to store and release more electrical energy per unit volume or mass. Experimental verification shows that the iodine positive electrode with a positively charged CEI layer has significant improvements in battery capacity and cycle life compared to the prior art. For example, in a specific embodiment, the battery capacity can be increased to 156.2mAh g -1 As mentioned above, the cycle life can exceed 1000 times, which fully proves the effectiveness and superiority of the technical solution of the present invention in improving the performance of zinc-based halogen batteries, and provides strong support for the further development of zinc-based halogen battery technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 : is a schematic diagram of the positively charged CEI layer of the present invention being used to inhibit the shuttle effect of iodine active substances.

[0019] Figure 2 : Comparison of charge and discharge performance under current density.

[0020] Figure 3 : At 2A g -1 Comparison of charge and discharge performance under different current densities. DETAILED DESCRIPTION

[0021] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0022] Example 1

[0023] Activated carbon (AC), Ketjen black and binder polyvinylidene fluoride (PVDF) were uniformly dispersed in an organic solvent N-methyl-2-pyrrolidone (NMP) at a mass ratio of 7:2:1, and stirred at room temperature for 24 hours to prepare a uniformly dispersed mixed coating liquid.

[0024] The mixed coating liquid prepared in step 1 was coated on the current collector titanium mesh by a doctor blade method as the host material of the iodine active substance, and dried at 80°C until the organic solvent NMP evaporated completely. The loading amount of the host material after drying was about 15.5 mg / cm 2 .

[0025] A ZnI2+KI mixed solution (ZnI2 and KI concentrations were both 0.5 M) was used as the electrolyte, and a two-electrode constant current electroplating method (current was 6 mA / cm 2 , electroplating time is 31.0min), iodine is deposited on the titanium mesh coated with the host material prepared in step 2, and then vacuum dried at room temperature to prepare a high-loaded iodine positive electrode. The iodine loading of the positive electrode after drying is about 14.4mg / cm 2 .

[0026] The organic polymer containing positive charge is dispersed in water (the dispersion amount of the positive charge polymer in water is 10 mg / mL), and is evenly dispersed by ultrasonic treatment, and is evenly coated on the surface of the iodine positive electrode by drop coating. After vacuum drying, a high-loaded iodine positive electrode with a positively charged CEI layer can be obtained. The preferred CEI layer loading is 1.1 mg / cm 2 .

[0027] Activated carbon, Ketjen black and binder (mass ratio 7:2:1) were uniformly dispersed in NMP organic solvent, then uniformly coated on the titanium mesh current collector and dried at 80°C until NMP was completely volatilized. Iodine was deposited on the host material by constant current electroplating, and an iodine positive electrode was obtained after vacuum drying, with an iodine loading of about 4.9 mg / cm 2 The positively charged organic polymer was evenly dispersed in water by ultrasound, and coated on the surface of the prepared iodine positive electrode by drop coating. After vacuum drying, the CEI layer was successfully constructed. Performance test: The prepared I2@CEI positive electrode was used to assemble a zinc-iodine full battery, with zinc sheet as the negative electrode, 2M ZnSO4 as the electrolyte, and glass fiber as the separator. At 3A g -1 At the current density, the battery capacity reaches 156.2mAh g -1 , and can run stably for more than 1000 cycles.

[0028] Comparative Example 1

[0029] Performance test: The prepared I2@CEI positive electrode was used to assemble a zinc-iodine full battery, with zinc sheet as the negative electrode, 2MZnSO4 as the electrolyte, and glass fiber as the separator. -1 At the current density, the battery capacity is 152.2 mAh g -1 , and can run stably for 446 cycles.

[0030] Example 2

[0031] Activated carbon, Ketjen black and binder (mass ratio 7:2:1) were uniformly dispersed in an organic solvent, then coated on the surface of the titanium mesh current collector and dried at 80°C until NMP was completely volatilized. Iodine was deposited on the host material by constant current electroplating and used as an iodine positive electrode after vacuum drying. The iodine loading was about 14.4 mg / cm 2 The positively charged organic polymer was evenly dispersed in water by ultrasound, and coated on the surface of the iodine positive electrode by drop coating. After vacuum drying, the CEI layer was successfully constructed.

[0032] Performance test: A zinc-iodine full battery was assembled using a high-load I2@CEI cathode, with zinc sheet as the anode, 2M ZnSO4 as the electrolyte, and glass fiber as the separator. -1 At the current density, the battery capacity is 146.1 mAh g -1 , cycle life exceeds 600 times.

[0033] Comparative Example 2

[0034] Performance test: A zinc-iodine full battery was assembled using a high-load I2 positive electrode, a zinc sheet as the negative electrode, 2M ZnSO4 as the electrolyte, and glass fiber as the separator. -1 At the current density, the battery capacity reaches 92.1 mAh g -1 , the overall cycle life is 294 times.

[0035] It can be seen from the experimental results of the above embodiments and comparative examples that the iodine positive electrode with a positively charged CEI layer has obvious advantages in battery capacity and cycle life, which strongly proves the feasibility and effectiveness of the technical solution of the present invention.

[0036] In the performance test process of the embodiments and comparative examples, by Figure 2 and attached Figure 3 The charge and discharge curves shown in the figure are monitored and analyzed to accurately obtain the key performance indicators such as the capacity and cycle life of the battery, thereby verifying the superiority of the high-load iodine positive electrode with a positively charged CEI layer constructed by the present invention in the zinc-iodine battery. Figure 2 Curve data, at 3A g -1 At this current density, the battery's charging and discharging process is smooth, and the capacity remains stable at 156.2 mAh g -1 When the cycle number exceeds 1000, the curve still shows no obvious attenuation trend, indicating that the battery has good cycle stability; while the curve of comparative example 1 begins to show a rapid capacity decline after 446 cycles, indicating that the performance of the iodine positive electrode without a CEI layer deteriorates significantly during long-term cycles. Figure 3The same conclusion can be drawn from the curve comparison between Example 2 and Comparative Example 2, which further proves the effectiveness and innovation of the technical solution of the present invention.

Claims

1. A method for inhibiting the shuttle effect of positive active materials in zinc-based halogen batteries, characterized in that: The method includes in-situ constructing a positively charged CEI layer on the surface of the iodine positive electrode, and through surface charge regulation, causing the positively charged CEI layer to produce electrostatic adsorption with the polyiodine anions in the positive electrode to inhibit the shuttling effect of iodine active substances under high load conditions.

2. The method according to claim 1, characterized in that The positively charged CEI layer is constructed by the following steps: uniformly dispersing an organic polymer containing a positive charge in water, uniformly coating it on the surface of an iodine positive electrode by a drop coating method, and vacuum drying to obtain a high-loaded iodine positive electrode having a positively charged CEI layer.

3. The method according to claim 2, characterized in that The high-loaded iodine positive electrode with a CEI layer is prepared by the following steps: (1) Activated carbon (AC), Ketjen black and binder polyvinylidene fluoride (PVDF) were uniformly dispersed in an organic solvent N-methyl-2-pyrrolidone (NMP) at a mass ratio of 7:2:1, and stirred at room temperature for 24 hours to prepare a uniformly dispersed mixed coating liquid; (2) The mixed coating liquid prepared in step (1) is applied to the current collector titanium mesh as the host material of the iodine active substance, and dried at 80° C. until the organic solvent NMP is completely evaporated. The host material loading after drying is about 15.5 mg / cm 2 ; (3) Using a ZnI2+KI mixed solution as the electrolyte, a two-electrode constant current electroplating method was used to deposit iodine on the titanium mesh coated with the host material prepared in step (2), and then vacuum dried at room temperature to prepare a high-loaded iodine positive electrode. The iodine loading of the positive electrode after drying was about 14.4 mg / cm 2 ; (4) dispersing the organic polymer containing positive charge in water, making it uniformly dispersed by ultrasonic treatment, and uniformly coating it on the surface of the iodine positive electrode by drop coating, and then vacuum drying to obtain a high-load iodine positive electrode with a positively charged CEI layer. The preferred CEI layer loading is 1.1 mg / cm 2 .

4. The method according to claim 3, characterized in that In step (3), the concentrations of ZnI2 and KI in the electrolyte are both 0.5 M, the electroplating time is 31.0 min, and the current is 6 mA / cm 2 .

5. The method according to claim 3, characterized in that: In step (4), the dispersion amount of the positively charged polymer in water is 10 mg / mL.

6. A high-loaded iodine positive electrode with a CEI layer prepared by the method according to any one of claims 1 to 5, characterized in that: The iodine active material loading is 14.4 mg cm-2, and the corresponding CEI layer loading is 1.1 mg cm-2.

7. A zinc-iodine battery, characterized in that: It comprises the high-loaded iodine positive electrode with a CEI layer as described in claim 6, a zinc sheet negative electrode, a 2M ZnSO4 electrolyte and a glass fiber separator.

8. An application of the method for constructing a positively charged CEI layer according to any one of claims 1 to 5 in a zinc-based halogen battery, characterized in that: By constructing a positively charged CEI layer on the surface of the iodine positive electrode and utilizing the strong physical and chemical adsorption effect between it and the iodine active substance, the loading capacity of the iodine positive electrode is increased, thereby improving the energy density of the zinc-based halogen battery.

9. The use according to claim 8, characterized in that: The zinc-based halogen battery is a zinc-bromine battery, which improves the performance of the zinc-bromine battery by constructing a positively charged CEI layer on the surface of the bromine positive electrode to prevent the shuttling of bromine active substances.

Citation Information

Patent Citations

  • High-performance chargeable-dischargeable aqueous zinc-iodine battery and preparation method thereof

    CN113782710A

  • Halogen positive electrode, preparation method and zinc-halogen battery

    CN118693219A

  • Shuttling-free batteries and preparation method thereof

    WO2024055059A1